Nonuniform Finite Difference Scheme for the Three-Dimensional Time-Fractional Black–Scholes Equation. (24th December 2021) - Kim, Sangkwon; Lee, Chaeyoung; Lee, Wonjin; Kwak, Soobin; Jeong, Darae; Kim, Junseok
Abstract : In this study, we present an accurate and efficient nonuniform finite difference method for the three-dimensional (3D) time-fractional Black–Scholes (BS) equation. The operator splitting scheme is used to efficiently solve the 3D time-fractional BS equation. We use a nonuniform grid for pricing 3D options. We compute the three-asset cash-or-nothing European call option and investigate the effects of the fractional-order α in the time-fractional BS model. Numerical experiments demonstrate the efficiency and fastness of the proposed scheme.